Examine The effect of Job Satisfaction on The Performance of Hospital Employees Through Organizational Commitment - Fatmah Bagis (LPPM ITB AAS INDONESIA (d.h STIE AAS Surakarta), 2022)
Expectancy theory is used in this study to link the effect of job satisfaction on the performance of hospital nurses mediated by organizational commitment. The study was conducted with 150 nurse respondents from two different hospitals in Banyumas Regency. The results show that job satisfaction and organizational commitment have a negative and insignificant effect on nurse performance. And job satisfaction has a positive and significant effect on organizational commitment. The results also show that organizational commitment cannot mediate the effect of job satisfaction on nurse performance. Keywords: nurse performance, organizational commitment, job satisfaction, employee performance.